Increasing Productivity in Planting Indigofera Tinctoria Plant Seeds as Producers of Natural Dyes in Pacarejo Village, Semanu, Gunung Kidul, D.I. Yogyakarta - Supriadianto, Supriadianto; Rahayuningsih, Edia; Dewi, Kumala; Pamungkas, Mukmin Sapto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
This investigation was conducted in Pacarejo Village with the participation of thirty people. This activity was a follow-up to the second year of research, with the objectives of: 1) Increasing participation and strengthening the commitment of Gapoktan of Sembada, Pacarejo Village by planting Indigofera tinctoria as an alternative plant with a fixed price that can improve people's income, 2) Realizing additional land, provision of seeds, and matrices for planting Indigofera tinctoria plants to meet the availability of sustainable raw materials, and 3) Providing assistance in care. The expected outputs to achieve an independent village are as follows: 1) Realization of a Cooperation Agreement for planting Indigofera tinctoria on at least 2 hectares, 2) Development of a planting system, plant care, and harvesting methods with optimal and sustainable quality, and 3) Availability of natural dye raw materials extracted from Indigofera tinctoria leaves that meet raw material quality standards and are sustainable. This research effectively improved the well-being of the residents of Calonejo Village, particularly the Gapoktan Sembada, Pacarejo Village by increasing the Indigofera plant nursery productivity of farmers. This research was successful due to the conclusion of a cooperation agreement to plant Indigofera tinctoria on an area of 3 hectares, the establishment of a planting system, plant care, and harvesting methods with optimal and sustainable quality, and the availability of raw materials for natural dyes extracted from Indigofera tinctoria leaves with optimal and sustainable quality. Information session, Group Discussion Forums (FGD), Training, and Direct Assistance methods are used.